Interdecadal analysis of the performance of reference evapotranspiration estimation methods in Bom Jesus/PI - Gonçalves Júnior, Angelo da Silva (2022)
The reference evapotranspiration is an important variable whose estimation is of great relevance for the management of water resources in a sustainable way. The objective was to evaluate the performance of different methods of estimating reference evapotranspiration, on the interdecadal scale, in the municipality of Bom Jesus/PI. Data on meteorological variables were obtained through the NASA-POWER platform (1981 to 2020) and divided into decade intervals (I - 1981 to 1990; II - 1991 to 2000; III - 2001 to 2010 and IV - 2011 to 2020). The methods analyzed were Andrade Júnior, Benavides-Lopez, Camargo, Hamon, Hargreaves-Samani, Jensen-Haise and Linacre, which were compared to the Penman-Monteith FAO56 method, which is the standard method. Determination and correlation coefficients, agreement and performance indices and standard error of estimate were calculated. It was observed that the Camargo and Hamon methods were classified according to the performance index as very bad in all the analyzed decades. Linacre, Benavides-Lopez and Andrade Júnior's methods ranged in their performance rating from very good to excellent. The Linacre method was the one that presented the best independent performance of the analysis decade, being, therefore, recommended for estimating the reference evapotranspiration in the municipality of Bom Jesus, Piauí.